Purchase Decision of Surakarta and Salatiga's Generation Z Muslims: Halal Literacy and Halal Awareness - Qurniawati, Rina Sari; Permadi, Dina Trifiana; Nurohman, Yulfan Arif (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Increasing the Indonesian people's awareness level at the level of halal awareness impacts the rising demand for halal products. Consumers in the understanding of halal or haram products are limited to the halal label, even though they are not necessarily verified as halal. Generation Z, which has characteristics familiar with technology and high curiosity, turns out to have a low level of religiosity compared to other generations. This study examines and explains the role of halal awareness in mediating the relationship between halal literacy and purchasing decisions. The number of samples in this study amounted to 125 Muslim generation Z respondents from Salatiga and Surakarta, obtained using a purposive sampling technique. This study used a path analysis technique with SmartPLS version 3 software. The results showed that halal literacy and awareness proved to have an effect on purchasing decisions while religiosity was not a moderating variable. BPJPH must inform the guidelines for submitting the halal logo and simplify the management so that more entrepreneurs use the official halal logo.